Effects of Nervilia fordii Extract on Pulmonary Fibrosis Through TGF-β/Smad Signaling Pathway - Yao, Yufeng; Yuan, Yue; Lu, Zenghui; Ma, Yunxia; Xie, Yuanyuan; Wang, Meiqi; Liu, Fangle; Zhu, Chenchen; Lin, Chaozhan (Frontiers in Pharmacology, 2021)
Idiopathic pulmonary fibrosis (IPF) is a progressive and irreversible interstitial pulmonary disease with a poor prognosis. The extract of Nervilia fordii (NFE) has shown remarkable benefit in the treatment of acute lung injury, lung cancer, and severe acute respiratory syndrome (SARS). However, the potential mechanism and efficacy of NFE in the treatment of IPF remain unknown. In this study, a systematic network pharmacology analysis was used to predict the mechanism and efficacy of NFE in the treatment of IPF, based on the major components of NFE elucidated by UPLC-TOF-MS/MS. The potential molecular interactions between the compounds and potential targets were predicted using molecular docking. In vivo, rats with pulmonary fibrosis induced by a single intratracheal injection of bleomycin (BLM) were orally administered NFE for 14 days. Lung index and biochemical levels were determined, and histopathological analysis using hematoxylin and eosin (H&E) and Masson staining was performed. The effects of NFE on fibroblast proliferation in Lipopolysaccharide (LPS)- and TGF-β1-induced mouse 3T6 fibroblasts were evaluated in vitro. In total, 20 components were identified in NFE, and 102 potential targets for IPF treatment were predicted. These targets potentially participate in processes regulated by transmembrane receptor protein tyrosine kinase, ERBB2, and et al. Molecular docking results predicted high affinity interactions between three components (rhamnazin, rhamnetin, and rhamnocitrin) and the potential targets, suggesting that TGF-β is the most important potential target of NFE in the treatment of pulmonary fibrosis. NFE significantly decreased the lung index and alleviated BLM-induced pulmonary fibrosis in rats. Histopathological observation of lung tissues showed that NFE alleviated inflammation and collagen deposition in BLM-induced rats. NFE inhibited the migration of LPS- and TGF-β1-induced 3T6 fibroblasts, reduced the contents of hydroxyproline and collagen, and contributed to anti-inflammation and anti-oxidation. With the intervention of NFE, the protein and RNA expression of TGF-β1, α-SMA, Smad3/4, p-Smad3/4, CTGF and p-ERK1/2 were significantly downregulated, while Smad7 and ERK1/2 were upregulated significantly in vivo and in vitro. These findings indicated that NFE may exert therapeutic effects on pulmonary fibrosis by alleviating inflammation, oxidation, and collagen deposition. The mechanism related to the inhibition of the TGF-β/Smad signaling pathway.